PREVALENCE AND CHARACTERISTICS OF METABOLIC SYNDROME PATIENTS IN CIBEBER VILLAGE CIMAHI INDONESIA - Iis Inayati Rakhmat; Hadi Jusuf; Sinta Rachmanita (Fakultas Kedokteran Gigi Unjani, 2021)
Metabolic syndrome is a health problem that often occurs among populations in Indonesia.Dataon the characteristics of patients with metabolic syndrome is still very limited, despite the importance of cardiovasculardiseaseprevention.The study aims to explain the prevalence and characteristics of patients with metabolic syndrome in Indonesia.The research methodology used descriptive research using a cross-sectional design. The number of respondents was seven men and 34 women, counted by consecutive sampling. The data was collected from the SQ-FFQ questionnaire and calculating the DQI-I score, analyzing physical activity through the GPAQ questionnaire converted into METs, measuring blood pressure, taking blood, measuring waist circumference, measuring fasting blood sugar. Through enzymatic tests, Serum triglyceride levels through the enzymatic colorimetric GPO-PAP test and HDL cholesterol levels were measured by the CHODPAP method. The results showed that the prevalence of SM was 20.45%, and the majority were women. The largest age group were the elderly. Most cases of metabolic syndrome have three components, with the largest components being central obesity (100%) and blood pressure (88.89%). Most categories of activity were moderate, and diet quality was low. All metabolic syndrome patients in this study were found not to smoke and not to consume alcohol. Based on these results, it can be concluded that SM incidence was high. Further research is needed regarding the relationship between acquired risk factors and metabolic syndrome. DOI : 10.54052/jhds.v1n1.p27-37